Mediating of Organizational Commitment in Improving Employee Performance - Wahid, Ayi; Vivi Afifah (International Journal of Advanced Multidisciplinary, 2022)
The purpose of this research was to determine and analyze the effect of leadership style and work motivation simultaneously or partially on organizational commitment, as well as the implications for employee performance at hospitality industry. The population in this study were employees of hospitality industry in Bandung West Jaba. The research method used in this research was descriptive and explanatory survey methods with a sample of 79 respondents, and the data analysis method used was path analysis using SPSS version 20 data processing software. Based on the results of the research found that the leadership style and work motivation simultaneously or partially have a positive and significant effect on organizational commitment, partially work motivation was the most dominant variable affecting the organizational commitment. Organizational commitment has a positive and significant effect on employee performance. Another important finding of this research was that the leadership style and work motivation indirectly have a positive and significant effect on employee performance through organizational commitment.